The importance of an illicit drug history in the evaluation of suspected spontaneous pneumothorax. - Shah,A; Paramlal,M (BMJ Case Rep, 2011)
The authors present the case of a 27-year-old man who presented with acute left-sided pleuritic chest pain and dyspnoea managed as for a spontaneous pneumothorax with aspiration and subsequent chest drain insertion following a chest radiograph. Despite intervention, however, his chest radiograph showed what appeared to be a non-resolving pneumothorax. Further history revealed a large cannabis smoking exposure and subsequent CT imaging revealed large apical bullous disease with little residual pneumothorax. The patient was referred for cardiothoracic bullectomy and pleurodesis. The authors review the association between cannabis smoke inhalation and apical bullous lung disease and stress the importance of direct questioning on initial history. If a significant history is found, the authors argue that CT imaging and primary cardiothoracic intervention may then be the investigation and management of choice in a stable patient.